c.1 - Morris, Christopher (London, 1953)
IN one sense sixteenth-century Englishmen had no political theory whatsoever, for they had no theory of what we call the State. The theories they had were theories of Society. They discussed the offices of certain persons in Society, of king or noble, priest or magistrate. They discussed the ends, natural and supernatural, which Society was meant to serve. They discussed the character, the origins, and the inter relationship of various sorts of law which held good in Society and of various authorities with which Society confronted its members. Most of all they discussed the importance to Society of obedience to authority, although they remained aware of limits which, in a healthy society, no authority would think of over stepping. The King, moreover, was only one of the authorities. There were others-the Law, the People, the Church, God, and (according to some thinkers) Conscience. None of these authorities had as yet been conflated or confused with any other; and the problem facing social theorists was that of rendering to each authority its due.
Keywords: Political Thought-England